2014
DOI: 10.1155/2014/618382
|View full text |Cite
|
Sign up to set email alerts
|

Tamponade or Filling Effect: Changes of Forces in Myopic Eyes

Abstract: Myopia is the most common ocular abnormality. Its high and growing prevalence has contributed to a recent surge in surgical interest in the disorder, since retinal detachment in eyes with high myopia differs from that in emmetropic eyes or eyes with low myopia. The myopic eye, because of its specific anatomy, poses special challenges that need to be overcome to ensure the appropriate use of vitreous substitutes. However, intraocular tamponades have shown great potential for revolutionizing retinal detachment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 131 publications
0
19
0
Order By: Relevance
“…; Semeraro et al. ). Microemulsion is suspected to trigger chemotaxis of inflammatory cells and phagocytosis that stimulate a foreign body‐type reaction and consequent phagocytosis by macrophages.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…; Semeraro et al. ). Microemulsion is suspected to trigger chemotaxis of inflammatory cells and phagocytosis that stimulate a foreign body‐type reaction and consequent phagocytosis by macrophages.…”
Section: Discussionmentioning
confidence: 96%
“…Side‐effects of heavy silicone oil (HSO) are associated with the chemical and physical properties of the tamponading compound and are similar to those associated with conventional silicone oil (Semeraro et al. ). Four main mechanisms are reported in the genesis of the inflammatory reaction to standard and HSO: direct toxicity and immunogenicity, toxicity due to impurities or instability of the agent, oil emulsification and mechanical injury due to gravity (Mackiewicz et al.…”
Section: Introductionmentioning
confidence: 99%
“…Myopia is associated with vitreous liquefaction excessive in relation to the degree of vitreoretinal adhesion, resulting in anomalous PVD and traction at vitreoretinal interface [ 13 ] ( Figure 2 ). In high myopia, the anteroposterior axis is the longest, and the vitreous chamber may be prolate [ 32 ]. Meskauskas et al suggested that elongation and enlargement of the vitreous chamber might increase the vitreous and retinal shear stress exerted by the movement of the eye, playing an important role in the pathogenesis of PVD and retinal detachment (RD) [ 33 ].…”
Section: Anomalous Posterior Vitreous Detachment and Vitreoschisismentioning
confidence: 99%
“…The vitreous, partially liquefied, is more rapidly disrupted in larger eyes than in normal eyes [ 32 ]. This process leads to a significant reduction in the gel volume and a consequent increase in the liquid volume, which results in PVD or posterior vitreoschisis, whereas the increased rigidity of the preretinal vitreous might be the cause of undue tangential traction at the vitreoretinal interface either at the posterior pole or in the middle periphery [ 13 , 32 ]. Furthermore, in highly myopic eyes, when PVD occurs, sheets of residual cortical vitreous often remain attached to the inner surface of the retina.…”
Section: Anomalous Posterior Vitreous Detachment and Vitreoschisismentioning
confidence: 99%
“…The eyes with high myopia are at higher risk of developing into rhegmatogenous retinal detachment (RRD) for a number of reasons (Semeraro et al 2014): (1) a weak attachment between the neurosensory retina and the retinal pigment epithelium in the elongation of the vitreous chamber, especially posterior staphyloma. (2) The vitreous and retinal shear stresses in the enlargement and elongation of the vitreous chamber are increased by the movement of the eye, which may cause high myopic eyes more prone to develop posterior vitreous detachment and retinal detachment.…”
mentioning
confidence: 99%